The epidemiology of sepsis in Brazilian intensive care units (the Sepsis PREvalence Assessment Database, SPREAD): an observational study - Machado, Flavia R. (2017)
Fernando Augusto Bozza. Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Documento produzido em parceria ou por autor vinculado à Fiocruz, mas não consta a informação no documento.